2009
DOI: 10.1136/tc.2009.030445
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of a social contract smoking prevention program among children in Québec, Canada

Abstract: Mission TNT.06 may encourage young smokers to misreport their smoking status and to marginalise classmates who smoke. These findings prompted recommendations to conduct more in-depth evaluation of the smoke-free class competition before widespread dissemination of the program across the province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Failure to do so could lead to interventions that are fundamentally flawed because they do not address the full range of factors known to be associated with smoking onset. Indeed, the mitigated results of evaluations of even the most carefully conceptualized and well-funded tobacco control interventions [1][2][3][4][5] may reflect a lack of comprehensive action that address relevant risk factors at the individual and environmental levels. It will be important to distinguish modifiable risk factors (e.g., exposure to family and friends' smoking, exposure to films) from those that are not modifiable (e.g., age or sex) but may be helpful in terms of targeting intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to do so could lead to interventions that are fundamentally flawed because they do not address the full range of factors known to be associated with smoking onset. Indeed, the mitigated results of evaluations of even the most carefully conceptualized and well-funded tobacco control interventions [1][2][3][4][5] may reflect a lack of comprehensive action that address relevant risk factors at the individual and environmental levels. It will be important to distinguish modifiable risk factors (e.g., exposure to family and friends' smoking, exposure to films) from those that are not modifiable (e.g., age or sex) but may be helpful in terms of targeting intervention.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several recent reviews reinforce that the impact of school-based and other types of targeted prevention programs are often short-term, 1,3 and some studies suggest that such prevention efforts may have unanticipated negative effects. 4,5 These observations may reflect a lack of comprehensive understanding of the factors associated with onset such that tobacco control interventions are not conceptualized optimally.…”
Section: Contextmentioning
confidence: 99%
“…The remaining 14 studies were reviewed in more detail on the basis of the full text. Among them six records were excluded since the report data was from trials without a control group or without any original data at all [23,24,25,26,27,28], two trials were excluded since they did not report the pre-defined outcome [29,30] and one record was excluded since it reported only on the sub-analyses of another trial [31]. Finally, five studies were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies had certain limitations such as the inclusion of only two studies (Kavanagh et al, 2011), and not adjusting for clustering . There are also some concerns about class competitions fostering an atmosphere of dishonesty, suspicion (Etter and Bouvier, 2006;Kairouz et al, 2009) and bullying, although other studies have not found negative peer pressure or bullying (Hanewinkel et al, 2010). Given the strong peer influence among adolescents, interventions at the class, year group or whole of school level that provides a supportive social environment may be a key element to motivate behaviour change (Silva et al, 2014).…”
Section: Effectiveness Of Competitionmentioning
confidence: 99%